Identification of Mitochondrial DNA Variants Associated With Risk of Neuroblastoma. (2nd February 2022) - Chang, Xiao; Liu, Yichuan; Glessner, Joseph; Hou, Cuiping; Qu, Huiqi; Nguyen, Kenny; Sleiman, Patrick; Lee, Lobin; Diskin, Sharon J; Maris, John M; Hakonarson, Hakon
Abstract: Neuroblastoma is a childhood cancer that originates in the developing sympathetic nervous system. We previously reported a crucial role of mitochondrial DNA haplogroups in the pathology of neuroblastoma. To pinpoint mitochondrial DNA variants associated with neuroblastoma risk, we applied a mitochondrial genome imputation pipeline to the single nucleotide polymorphisms array data of 2 pediatric cohorts containing a total of 2404 neuroblastoma patients and 9310 cancer-free controls. All statistical tests were 2-sided. The single nucleotide variant, rs2853493, was statistically significantly associated with neuroblastoma risk in the discovery cohort (odds ratio = 0.62, 95% confidence interval = 0.53 to 0.72, P < .001) and further confirmed in the replication cohort (odds ratio = 0.75, 95% confidence interval = 0.62 to 0.90, P = .002). Further, expression quantitative trait loci analysis indicated genotypes of rs2853493 were associated with expression levels of MT-CYB gene expression in neuroblastoma cells, suggesting rs2853493 may confer risk to neuroblastoma via regulating the expression level of its nearby genes.